Preobrazovanie prirody v SSSR - Tsvetkova, L. (Soviet Union : Tsentrnauchfilm, 1982)
The film presents and justifies the plan to change the course of the Siberian rivers to create an irrigation system in the Central Asian deserts.
Start: 01:06:00, End: 01:26:00
With voice-over in Hungarian